Perianal Langerhans cell histiocytosis: a rare presentation in an adult male - Abdou, Asmaa Gaber; Taie, Doha Maher (Autopsy and Case Reports, 2017)
Langerhans cell histiocytosis (LCH) is a rare disease characterized by a proliferation of cells that show immunophenotypic and ultrastructural similarities with antigen-presenting Langerhans cells of mucosal sites and skin. LCH in adults is rare, and there are still many undiagnosed/misdiagnosed patients. We describe LCH involvement of the perianal region of a 33-year-old male with a previous history of diabetes insipidus. The differential diagnosis and all the reported cases of LCH of the perianal skin involvement since its description in 1984 till 2016 are discussed. LCH should be considered in the differential diagnosis of perianal ulceration, especially in young patients where topical drug treatment has failed. The history of previous central diabetes insipidus of unknown etiology demands imaging studies in order to rule out central involvement of the disease